The answer is 10 because 5×2 is 10 and 10 times one is 10. So that's the lowest common denominator her.
Hello there!
3x - y = 3
-x + y = 3
We need to solve 3x - y = 3 for y
Let start by adding -3x to both sides
3x - y = 3
3x - 3x - y = 3 - 3x
-y = 3 - 3x
We cannot leave the variable with a negative sign. We must multiply both sides by -1
-y * -1= (3 - 3x)-1
y = 3x - 3
Substitute 3x -3 for y in -x+y=3
-x + y = 3
-x + 3x - 3 = 3
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6/2
x = 3
Now substitute 3 for x in y=3x -3
y = 3x - 3
y = 3(3) - 3
y= 9 - 3
y= 6
Thus,
The answer is x=3 and y=6
It is always my pleasure to help students like you :)
As always, I am here to help!
4(x-3)-(2x+5)=-3x-27
4*x - 4*3 - 2x - 5 = -3x - 27
4x - 12 - 2x - 5 = -3x - 27
2x - 17 = -3x - 27
2x + 3x = -27 + 17
5x = -10 / : 5
x = -2
0.1111 if you want it as a decimal
Answer:
![about \: 1.01551](https://tex.z-dn.net/?f=about%20%5C%3A%201.01551)
Step-by-step explanation:
No it isn't, because:
![{1.08}^{ \frac{1}{5} } = { \frac{108}{100} }^{ \frac{1}{5} } = { \frac{27}{25} }^{ \frac{1}{5} } = \sqrt[5]{ \frac{27}{25} } = 1.01551](https://tex.z-dn.net/?f=%20%7B1.08%7D%5E%7B%20%5Cfrac%7B1%7D%7B5%7D%20%7D%20%20%3D%20%20%7B%20%5Cfrac%7B108%7D%7B100%7D%20%7D%5E%7B%20%5Cfrac%7B1%7D%7B5%7D%20%7D%20%20%3D%20%20%7B%20%5Cfrac%7B27%7D%7B25%7D%20%7D%5E%7B%20%5Cfrac%7B1%7D%7B5%7D%20%7D%20%20%3D%20%20%5Csqrt%5B5%5D%7B%20%5Cfrac%7B27%7D%7B25%7D%20%7D%20%20%3D%201.01551)